Mechanotransductive cascade of Myo-II-dependent mesoderm and endoderm invaginations in embryo gastrulation - Mitrossilis, Démosthène (Nat Commun, 2017)
Animal development consists of a cascade of tissue differentiation and shape change. Associated mechanical signals regulate tissue differentiation. Here we demonstrate that endogenous mechanical cues also trigger biochemical pathways, generating the active morphogenetic movements shaping animal development through a mechanotransductive cascade of Myo-II medio-apical stabilization. To mimic physiological tissue deformation with a cell scale resolution, liposomes containing magnetic nanoparticles are injected into embryonic epithelia and submitted to time-variable forces generated by a linear array of micrometric soft magnets. Periodic magnetically induced deformations quantitatively phenocopy the soft mechanical endogenous snail-dependent apex pulsations, rescue the medio-apical accumulation of Rok, Myo-II and subsequent mesoderm invagination lacking in sna mutants, in a Fog-dependent mechanotransductive process. Mesoderm invagination then activates Myo-II apical accumulation, in a similar Fog-dependent mechanotransductive process, which in turn initiates endoderm invagination. This reveals the existence of a highly dynamic self-inductive cascade of mesoderm and endoderm invaginations, regulated by mechano-induced medio-apical stabilization of Myo-II.